Maximizing the expected remaining useful lifetime of a weakly controlled device. Issue 9 (1st September 2020) - Lefebvre, Mario
Abstract : A degenerate two-dimensional diffusion process is considered as a model for the amount X ( t ) of deterioration at time t that a device can suffer before having to be repaired or replaced. The model is such that X ( t ) is strictly decreasing with time. Moreover, the deterioration rate is assumed to increase after a random amount of time. An approximate solution is sought to the problem of maximizing the expected remaining useful lifetime of the device when it is weakly controlled.